Prospective Clinical and Molecular Evaluation of Potential Plasmodium ovale curtisi and wallikeri Relapses in a High-transmission Setting. (19th April 2019) - Groger, Mirjam; Veletzky, Luzia; Lalremruata, Albert; Cattaneo, Chiara; Mischlinger, Johannes; Manego Zoleko, Rella; Kim, Johanna; Klicpera, Anna; Meyer, Elias L; Blessborn, Daniel; Winterberg, Markus; Adegnika, Ayola A; et al.
Abstract: Background: Plasmodium ovale curtisi and wallikeri are perceived as relapsing malarial parasites. Contrary to Plasmodium vivax, direct evidence for this hypothesis is scarce. The aim of this prospective study was to characterize the reappearance patterns of ovale parasites. Methods: P. ovale spp. infected patients were treated with artemether-lumefantrine and followed biweekly for up to 1 year for the detection of reappearing parasitemia. Molecular analysis of reappearing isolates was performed to identify homologous isolates by genotyping and to define cases of relapse following predefined criteria. Results: At inclusion, 26 participants were positive for P. ovale curtisi and/or P. ovale wallikeri . The median duration of follow-up was 35 weeks. Reappearance of the same P. ovale species was observed in 46% of participants; 61% of P. ovale curtisi and 19% of P. ovale wallikeri infection-free intervals were estimated to end with reappearance by week 32. Based on the predefined criteria, 23% of participants were identified with 1 or 2 relapses, all induced by P. ovale curtisi . Conclusion: These findings are in line with the currently accepted relapse theory inasmuch as the reappearance of P. ovale curtisi strains following initial blood clearance was conclusively demonstrated. Interestingly, no relapse of P. ovale wallikeri was observed. Abstract : The formation of hypnozoites and consequential relapse of tertian malaria is a widely accepted theory that lacks, however, confirmation for Plasmodium ovale spp. This study clinically and molecularly evaluates reappearing P. ovale spp. parasites to provide new evidence.